GAMBARAN PENGETAHUAN TENTANG TAMPILAN MALOKLUSI PADA SISWA SEKOLAH MENENGAH PERTAMA KRISTEN 67 IMANUEL BAHU - Djunaid, Ahmad; Gunawan, Paulina N.; Khoman, Johanna A. (e-GiGi, 2013)
Abstract: Malocclusion is a condition that deviates from normal occlusion include irregularity of the teeth in the dental arch such as crowding, protrusif, malposition and harmonious relationship with the opposing teeth. Occurrence of malocclusion in children will lead to many problems such as including impaired of mastication, speech processing as well as aesthetic problems socially impaired. The purpose of this study to describe the knowledge of malocclusion in junior high school 67 Christian Immanuel Bahu. The research is descriptive and sampling method with a total sampling methods. Retrieval of data to find a picture of malocclusions knowledge gained by means of questionnaires by a sample of 88 students. Knowledge of the research lookscale photographs by AC of IOTN in accordance with the composition of his teeth with persentse 44.31%, knowledge of tooth arrangement in accordance with the profile picture based on the percentage of 54.55% and a knowledge of  treatment  needs  in  accordance  with  the  percentage  of  23.87% appropriate Treatment needs. Keywords: knowledge, malocclusion.     Abstrak: Maloklusi merupakan keadaan yang menyimpang dari oklusi normal meliputi ketidakteraturan gigi-geligi dalam lengkung rahang seperti gigi berjejal, protrusif, malposisi maupun hubungan yang tidak harmonis dengan gigi antagonisnya. Terjadinya maloklusi pada anak akan mengakibatkan banyak masalah diantaranya gangguan pengunyahan, proses bicara serta masalah pergaulan karena estetik yang terganggu. Tujuan dari penelitian yaitu untuk mengetahui gambaran pengetahuan tentang maloklusi pada siswa SMP Kristen 67 Imanuel Bahu. Penelitian bersifat deskriptif dan cara pengambilan sampel dengan metode total sampling. Pengambilan data untuk mengetahui gambaran pengetahuan tentang maloklusi diperoleh dengan cara pengisian kuesioner oleh sampel yang berjumlah 88 siswa. Hasil penelitian didapatkan data pengetahuan tampilan berdasarkan skala fotograf AC dari IOTN sesuai dengan susunan giginya dengan persentse 44,31%, pengetahuan tentang susunan gigi sesuai berdasarkan foto profil dengan persentase 54,55% dan pengetahuan tentang kebutuhan perawatan dengan persentase 23,87% sesuai dengan kebutuhan perawatan. Kata kunci: pengetahuan, maloklusi.